Grey matter changes in patients with vestibular migraine. Issue 11 (November 2019) - Wang, S.; Wang, H.; Zhao, D.; Liu, X.; Yan, W.; Wang, M.; Zhao, R.
Abstract : AIM: To identify structural changes in the brain regions of patients with vestibular migraine (VM) so as to better understand its pathophysiology. MATERIAL AND METHODS: The differences in grey matter (GM) in patients with VM, patients with migraine without aura (MWoA), and healthy controls (HC) were investigated. Using a GE Signa 3 T magnetic resonance imaging (MRI) system, 3D structural images were acquired from 18 VM, 21 MWoA, and 21 age-, gender-, and education level-matched HC using a T1-weighted magnetization-prepared rapid acquisition gradient-echo (MPRAGE) sequence. The volumetric abnormalities of GM were estimated by voxel-based morphometry. Analysis of variance and Bonferroni multiple comparisons were applied. RESULTS: Compared with HC, patients with VM had significantly increased GM volume of the right medial superior frontal gyrus ( p= 0.008) and the right angular gyrus ( p= 0.009). Compared to patients with MWoA, patients with VM also had significantly increased volume of the right medial superior frontal gyrus ( p= 0.001), the right angular gyrus ( p= 0.008), and the left middle frontal gyrus ( p= 0.001). CONCLUSIONS: The GM volume of some brain regions of patients with VM is significantly larger than the other two groups. The increased GM volume in these brain regions in patients with VM may be related to self-adaptation of the nervous system, leading to an abnormal brain sensitization. Some of the brain regions with increased GM volume identified in this study were involved in assessment, integration, and expectations of pain and were strongly related to mood and anxiety. Highlights: There is no gray matter volume reduction region in the vestibular migraine patients. Many of the areas were involved in assessment, integration and expectations of pain. Areas of increased gray matter volume are associated with mood and anxiety.